Kualitas Extender Komersial yang dikombinasikan Filtrat Naga Merah (Hylocereus polyhizus) terhadap Semen Babi Landrace di Daerah Semiringkai - Foeh, Nancy D. F. K.; Gaina, Cynthia; Pandarangga, Putri; Datta, Frans Umbu; Tohpianong, Tarsisius C.; Deta, Herlina Umbu (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Artificial insemination with liquid semen in East Nusa Tenggara is still very rare, the Artificial insemination program is carried out using fresh semen. Liquid semen is generally stored at a temperature of 16-18 °C and lasts only a few days depending on the diluent used, for longer storage it requires the addition of antioxidants that can suppress the dangers of ROS. Therefore, this study was conducted to test the filtrate of red dragon (Hylocereus polyrhizus) in life semen diluent, which is expected to maintain the quality of spermatozoa in fresh semen. Semen was collected from 5 boars using the Glove Hand Method with Dummy Sow. Fresh semen that meets the SNI is diluted with the conditions of spermatozoa motility >70%, spermatozoa concentration >200,106 cells/ml and < abnormalities of 20%. The research was carried out in several stages: 1) examination of fresh semen 2) preparation of diluent 3) preparation of red dragon filtrate (Hylocereus polyrhizus) 4) manufacture of liquid semen. The data were analyzed descriptively and in a Complete Randomized Design with 5 treatments and 4 replicates. If there is a real difference, it can be continued with the Duncan test. Consecutive treatments: KO (fresh semen control); K1( Fresh semen control + semen life® ); P1 (fresh semen + semen life® + red dragon filtrate (Hylocereus polyhizu) 100μL); P2 (fresh semen + semen life® + red dragon filtrate (Hylocereus polyhizu) 200μL); P3 (fresh semen + semen life® + red dragon filtrate (Hylocereus polyhizu) 300μL); P4 (fresh semen + semen life® + red dragon filtrate (Hylocereus polyhizu) 400μL); P5 (fresh semen + semen life® + red dragon filtrate (Hylocereus polyhizu) 500μL). The results of the study can be concluded that the addition of red dragon phytrate (Hylocereus polyrhizus) 300μL in semen life® diluent has good effectiveness in maintaining the quality of liquid semen in storage at a temperature of 18-20 °C.